Application of generalized diffusion theory for calculation of particle distribution in suspension flow between two vertically coaxial cylinders - Phan, Nguyen Hong (Vietnam Journal of Mechanics, 2005)
Applications of the generalized diffusion theory for calculation of rotating spherical particle distribution in a suspension with viscouse fluid, using nonlinear closing relationships are demonstrated. A problem of motion of suspension in the gap between two rotating vertically coaxial cylinders was established and stationary case of the problem was numerically investigated. A comparison between the numerical prediction of particle concentration and the experimental data of Phillips et al. (1992) was made.